Standardization of a NaI(Tl) scintillation detector and its use on environments for Geology teaching in a Brazilian university - Barbosa, Eder Queiroz [UNESP]; Bonotto, Daniel Marcos [UNESP]; Roveratti, Gabrielle [UNESP] (Springer Nature, 2018)
This paper describes analytical protocols adopted for calibrating a portable gamma rays spectrometer using a 2ʺ × 2ʺ NaI(Tl) scintillation detector for performing exploration and environmental surveys. The steps involved the determination of counting times with good accuracy, calibration in energy and concentration, and data conversion to effective dose (Ed) for monitoring the radioactivity levels in the air, for indoor and outdoor environments. The χ2 test was applied to the counting rate data acquired for ten different readings, allowing determine the greater accuracy among them. Some standards yielded values above of the detection limit for calibrating the K, eU, and eTh windows, whereas empirical equations provided satisfactory results. The count rates in these windows were obtained in selected environments related to Geology teaching activities in a Brazilian university. Then, they were converted to Ed, showing the applicability of the adopted procedures for environmental surveys. The radiological monitoring showed two sites exhibiting Ed values above the WHO guideline reference value of 1 mSv/year. The first was in a minerals and rocks museum and the second in a deposit (litoteca) dedicated to the rocks storage. Thus, the members of the public are only occasionally exposed to the natural gamma radiation there. Additionally, the Ed values are much lower than the recommended limit of 20 mSv/year for occupationally exposed individuals.
Keywords: Calibration; Effective dose; K, eU, and eTh windows; NaI(Tl) scintillation detector; Portable gamma rays spectrometer